The Effectiveness of a Multi-Disciplinary Group Rehabilitation Program on the Psychosocial Functioning of Elderly People who are Visually Impaired. (January 2013) - Alma, Manna A.; Groothoff, Johan W.; Melis-Dankers, Bart J. M.; Suurmeijer, Theo P. B. M.; Van der Mei, Sijrike F.
Introduction: The pilot study reported here determined the effectiveness of a multidisciplinary group rehabilitation program, Visually Impaired Elderly Persons Participating (VIPP), on psychosocial functioning. Methods: The single-group pretest–posttest pilot study included 29 persons with visual impairments (aged 55 and older) who were referred to a low-vision rehabilitation center. The VIPP intervention (20 weekly meetings) consisted of four components (practical training; education, social interaction, counseling, and training in problem-solving skills; individual and group goal setting; and a home-based exercise program). Psychosocial adaptation to vision loss, helplessness, self-efficacy, mental health, and fear of falling were used as indicators of psychosocial functioning and were assessed at the baseline, halfway, immediately after completion of the intervention, and at the six-month follow-up. Results: Directly after the intervention, the participants' adaptation to vision loss (ES = 0.57), self-efficacy (ES = 0.50), and mental health (ES = 0.39) improved compared to the baseline. Moreover, helplessness and a generic and vision-specific fear of falling decreased (ES = 0.26, ES = 0.20, and ES = 0.24, respectively). The six-month follow-up measure indicated improved adaptation to vision loss (ES = 0.54), a lesser feeling of helplessness (ES = 0.53), better mental health (ES = 0.22), and a lesser vision-specific fear of falling (ES = 0.27). In contrast, a decrease in self-efficacy (ES = 0.14) and an increase in the generic fear of falling (ES = 0.18) were found. Discussion: The tentative conclusion of this small-scale pilot study is that the VIPP program benefits psychosocial functioning in both the short and long term. Implications for practitioners: The study showed that low-vision rehabilitation centers could implement multidisciplinary group rehabilitation programs, such as VIPP, to improve the psychosocial functioning of elderly people who are visually impaired.